PENGUKURAN KINERJA KEUANGAN PADA PT. BPR ARTHA SARI SENTOSA PERIODE 2013-2018 - Rizky Citra Dewi; Bambang Mursito; Istiatin Istiatin (ITB AAS INDONESIA Surakarta, 2020)
The aim of this research are to find out and explain how financial performance using rentability ratios, activity ratios, liquidity ratios, and solvency ratios at PT BPR Artha Sari Sentosa for the period 2013 - 2018. Types of data in this study are secondary data, data in the form of finance ratios of PT. BPR Artha Sari Sentosa for the period 2013 - 2018. Data collection techniques used in this research are documentation and literature study. Stages conducted by researchers to analyze the financial performance of PT. BPR Artha Sari Sentosa for the period 2013-2018 by calculating the financial ratios with each model. The results of this research are 1) Overall the rentability ratio of PT. BPR Artha Sari Sentosa is in very good condition, 2) The activity ratio of PT BPR Artha SariSentosa for the period of 2013-2018 is in very good condition, 3) The liquidity ratio in terms of the current ratio, in general, from 2013-2018 PT BPR Artha Sari Sentosa was in a pretty good position, 4) Overall the solvency ratio of PT BPR Artha Sari Sentosa was in very good condition. Keywords : rentability ratios, activity ratios, liquidity ratios, and solvency ratios.